Impact of Early Maladaptive Schemas on Motivational and Cognitive Components of Relationships - Kopaleishvili, M. Davood; Teona , Lodia (European Journal of Social Science Education and Research, 2024)
Early maladaptive schemas are cognitive structures formed in childhood, shaped by dysfunctional experiences that can lead to various behaviors often associated with mental disorders. This study investigates the role of maladaptive schemas in relational dynamics, focusing on cognitive and motivational structures. Key variables include: Self-determination: Assessed through autonomy and self-efficacy in relationships, categorized into autonomous, controlled, and impersonal dimensions; Normative beliefs about aggression: Evaluating maladaptive coping mechanisms, including both direct and indirect aggression. Trauma is acknowledged as a relevant factor in this model. Participants included adolescents and emerging adults (N = 214), aged 15 to 25, with nearly equal representation of male and female participants. Results indicate that higher levels of autonomous self-determination are associated with reduced normative beliefs regarding aggression. Overall, maladaptive schemas correlate with all forms of self-determination; specifically, disconnection/rejection and impaired autonomy schemas predict impersonal causality orientation, while impaired limits and overvigilance predict controlled self-determination. Using qualitative analysis alongside self-reported questionnaires, we explore the links between maladaptive schemas and individuals’ attempts to construct a narrative identity that provides meaning to their lived experiences. Findings suggest that for individuals with maladaptive schemas, narrative identity construction differs significantly.
Keywords: early maladaptive schemas, self-determination, aggression, narrative identity, trauma, adolescent development, cognitive structures